Bisphosphonate-Associated Mandibular Osteonecrosis - Carneiro, E.; Vibhute, P.; Montazem, A.; Som, P.M. (American Journal of Neuroradiology, 2006)
SUMMARY: A 66-year-old man with multiple myeloma treated with zoledronic acid, melphalan, and prednisone after a tooth extraction developed severe osteonecrosis of the mandible that was nonresponsive to antibiotic therapy. A CT scan showed innumerable fragmented sequestra in the mandible and some adjacent soft tissue fullness around the mandible. The association between the use of bisphosphonates and osteonecrosis of the jaw has been described only recently.